1998
DOI: 10.1074/jbc.273.38.24610
|View full text |Cite
|
Sign up to set email alerts
|

Differential Activation of p70 and p85 S6 Kinase Isoforms during Cardiac Hypertrophy in the Adult Mammal

Abstract: An adult feline right ventricular pressure overload (RVPO) model was used to examine the two S6 kinase (S6K) isoforms, p70 S6K and p85 S6K , that are involved in translational and transcriptional activation. Biochemical and confocal microscopy analyses at the level of the cardiocyte revealed that p70 S6K is present predominantly in the cytosol, substantially activated in 1-h RVPO (>12 fold), and phosphorylated in the pseudosubstrate domain at the Ser-411, Thr-421, and Ser-424 sites. p85 S6K , which was locali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
54
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 58 publications
6
54
0
Order By: Relevance
“…In the case of the p85 isoform, Thr-389 phosphorylation was significant in 4-and 24-h pressure-overloaded myocardium, whereas for the Thr-421/Ser-424 sites, significant phosphorylation was observed as early as 1 h and persisted up to at least 48 h of pressure overloading. The pattern of S6K1 activation matches precisely with our earlier studies performed under similar conditions (42). Overall, these data demonstrate once again that S6K1 is activated to a substantial level as early as 1 h of pressure overloading of the myocardium, and the activation is sustained for at least 24 h. Interestingly, the S6K1 activation is also accompanied by an increased mTOR phosphorylation at the Ser-2448 site.…”
Section: S6k1 Activation By C-raf/mek/erk Pathway In Adult Cardiomyocsupporting
confidence: 76%
See 3 more Smart Citations
“…In the case of the p85 isoform, Thr-389 phosphorylation was significant in 4-and 24-h pressure-overloaded myocardium, whereas for the Thr-421/Ser-424 sites, significant phosphorylation was observed as early as 1 h and persisted up to at least 48 h of pressure overloading. The pattern of S6K1 activation matches precisely with our earlier studies performed under similar conditions (42). Overall, these data demonstrate once again that S6K1 is activated to a substantial level as early as 1 h of pressure overloading of the myocardium, and the activation is sustained for at least 24 h. Interestingly, the S6K1 activation is also accompanied by an increased mTOR phosphorylation at the Ser-2448 site.…”
Section: S6k1 Activation By C-raf/mek/erk Pathway In Adult Cardiomyocsupporting
confidence: 76%
“…Several independent signaling pathways have been identified for S6K1 activation depending upon cell types and the nature of the stimulants (30 -36), and these pathways are activated subsequent to at least three independent agonists' stimulation: (i) TPA that activates a PKC-dependent pathway, (ii) insulin that activates a PI3K-dependent pathway, and (iii) forskolin that activates a protein kinase A (PKA)-dependent pathway. Activation of all these pathways has been demonstrated in pressure-overloaded myocardium by several research groups (58,61,(65)(66)(67), although our earlier study (42) demonstrated that the S6K1 activation was accompanied by the activation of PKC but not PI3K pathway in 1-to 4-h pressure overload myocardium. Therefore, we used cultured adult feline cardiocytes to explore the importance of potential downstream players of PKC, namely, c-Raf, MEK, and MAPK family members for S6K1 activation.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…12,13 Furthermore, S6K1 was activated in a cat model of right ventricular pressure overload, suggesting that mTOR or its target(s) might be involved in load-induced cardiac hypertrophy. 14 To determine the role of mTOR or its target(s) in load-induced cardiac hypertrophy, we administered a clinically relevant dose of rapamycin to mice subjected to ascending aortic constriction.…”
mentioning
confidence: 99%